USA-based retirement plan and its investment performance by an outsourcing company Datapath Ltd. - Hossain, MD. Sazid (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.